Managing the Workload: an Experiment on Individual Decision Making and Performance - Veronica Rattini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2016)
The present research investigates individual decision making regarding jobs scheduling, by means of a laboratory experiment based on the "Admission Test" of the University of Bologna, in which students have to allocate effort among several tasks in a limited timespan. The experiment includes three treatments that differ in the way the test is administered to participants: either with a fixed sequence of questions, or with a fixed time per task, or with no constraints. Results show large and significant heterogeneity in treatment effects. Constraints on the answering sequence or on the time allocation for each task improved the performance of those subjects who failed to efficiently allocate their effort among the tasks, whereas negative effects were found for students who were already good in self-organizing. The study has relevant policy implications for the organization of the workload in the labor force, when different types of workers are employed. Furthermore, important intuitions on the design of the university student-selection mechanisms are also discussed.
Keywords: J20; C91; I20; D80; C80; 330